Driving Employee Performance: The Interplay of Motivation, Leadership, and Organizational Culture in Enhancing Workforce Quality - Bhatt, Lok Raj (DAV Research Journal, 2026)
This study examines the relationship between motivation, leadership, and organizational culture on employee performance. This study analyzes what motivates people to work diligently at commercial banks. It examines how internal and external motivation influences employees and how different leadership styles, such as transactional leadership, affect the workforce at commercial bank. Additionally, this research looks into how commercial bank culture creates an impact for people working at the bank to perform effectively. The researchers collected quantitative data by administering a survey to 230 employees working at various divisions of Global IME Bank Limited in Kathmandu. Data were analyzed in SPSS using descriptive statistics and correlation and multiple regression analyses. There is a direct evidence that the culture within an organization has a strong effect on employees' performance, more than motivation, but less than leadership, but it does have a positive and significant impact on talent. The results support culture and motivation as a strong driver of performance while leadership influences performance only through motivating and creating a positive culture for individuals. Organizational culture and motivation strongly influence employee performance in banking, with leadership maintaining a symbiotic relationship. Culture and motivation can be enhanced with greater understanding. The banks can do things like creating more supportive cultures, implementing motivational programs tailored to their work forces and investing in developing leaders. An integrated strategy that tackles culture, motivation as well as leadership is preferred to accomplish the highest possible input from workers. However, this study contributes to HRM and organizational behavior literature, in displaying the different impacts of motivation, leadership and culture on employee performance considering a Nepalese banking context while establishing the correlation among these elements.